EFEKTIFITAS AROMATERAPI LEMON DALAM MENGURANGI MUAL DAN MUNTAH PADA IBU HAMIL TRIMESTER I TAHUN 2023 - Girsang, Rut Yohana (Journal of Midwifery Tiara Bunda, 2023)
The incidence of nausea and vomiting in pregnancy based on data from the World Health Organization (WHO, 2019) estimates that at least 14% of all pregnant women experience nausea and vomiting. The incidence of nausea and vomiting in pregnancy in Indonesia obtained from 2,203 pregnancies that could be completely observed is 534 pregnant women experienced nausea and vomiting. Knowledge is a result of human knowledge of the combination or collaboration between an object that knows and an object that is known. All that is known about a particular object (Suasumantri in Nurroh, 2019). Aromatherapy means therapy using essential oils whose extracts and chemical elements are taken in their entirety. Aromatherapy is part of herbal science (herbalism). (Poerwadadi, 2019) The type of research that will be used is the Descriptive Analytical research method with a cross sectional approach with a questionnaire instrument. This research was carried out at PMB Lia Zahara Amd. Skm District. The sample in this study was 37 respondents from first trimester pregnant women, using primary and secondary data. The sampling technique used Total Sampling with a population of 37. Data was collected by distributing questionnaires using univariate and bivariate analysis. The results of the study showed that there were pregnant women in the first trimester with the highest age being middle age (20-30 years) with the results being 24 (64.9%) pregnant women, pregnant women with the highest knowledge being good knowledge as many as 21 (56.8%) mothers pregnant, pregnant women with the highest parity were parity with 1-2 children as many as 17 (45.9%). This research is expected to increase mothers’knowladge and attitudes about the benefits of lemon as i non-pharmacological therapy in reducing nausea in first trimester pregnant women at PMB Lia Zahara Amd.Keb Skm in 2023